Identification of potential therapeutic targets in prostate cancer through a cross‐species approach - Sarah Jurmeister; Antonio Ramos‐Montoya; Chiranjeevi Sandi; Nelma Pértega‐Gomes; Karan Wadhwa; Alastair D Lamb; Mark J Dunning; Jan Attig; Jason S Carroll; Lee GD Fryer; Sérgio L Felisbino; David E Neal (EMBO Molecular Medicine)
Abstract Genetically engineered mouse models of cancer can be used to filter genome‐wide expression datasets generated from human tumours and to identify gene expression alterations that are functionally important to cancer development and progression. In this study, we have generated RNAseq data from tumours arising in two established mouse models of prostate cancer, PB‐Cre/PtenloxP/loxP and p53loxP/loxPRbloxP/loxP, and integrated this with published human prostate cancer expression data to pinpoint cancer‐associated gene expression changes that are conserved between the two species. To identify potential therapeutic targets, we then filtered this information for genes that are either known or predicted to be druggable. Using this approach, we revealed a functional role for the kinase MELK as a driver and potential therapeutic target in prostate cancer. We found that MELK expression was required for cell survival, affected the expression of genes associated with prostate cancer progression and was associated with biochemical recurrence.